2020
DOI: 10.1353/asr.2020.0005
|View full text |Cite
|
Sign up to set email alerts
|

Author Meets Critics: The Social Impact of Advertising: Confessions of an (Ex-)Advertising Man

Abstract: This Author Meets Critics conversation focuses on Tony Kelso's book The Social Impact of Advertising: Confessions of an (Ex-)Advertising Man (Rowman & Littlefield, 2019). Kelso meets with other advertising experts from several fields to discuss the following topics: what is meant by the social impact of advertising, the wealth of social and cultural topics covered in the book, using personal reflections in a textbook, the importance of history in understanding advertising, the effectiveness of digital adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The study revealed a noteworthy and unequivocal moderate relation between alcohol and drug curiosity and substance use risk among students in Gomoa West District and Effutu Municipal. This finding supports the argument of Kelso (2020), that many adolescents engaged This finding further confirmed the position of Fazio et al (1992), Green (1990), andLoewenstein (1994) that curiosity is a crucial motivational force in influencing human exploratory behaviors such as sexual activities, substance use, learning and increased brand recognition.…”
Section: Research Question Threesupporting
confidence: 84%
“…The study revealed a noteworthy and unequivocal moderate relation between alcohol and drug curiosity and substance use risk among students in Gomoa West District and Effutu Municipal. This finding supports the argument of Kelso (2020), that many adolescents engaged This finding further confirmed the position of Fazio et al (1992), Green (1990), andLoewenstein (1994) that curiosity is a crucial motivational force in influencing human exploratory behaviors such as sexual activities, substance use, learning and increased brand recognition.…”
Section: Research Question Threesupporting
confidence: 84%